Analysis of the flow produced by a low-Reynolds rotor optimezed for low noise applications - Part 1: Aerodynamics - Gourdain, N.; Serré, R.; Jardin, T.; Delattre, G.; Moschetta, J.-M. (My University, 2017)
The demand in Micro-Air Vehicles (MAV) is increasing as well as their potential missions. Whether for discretion in military operations or noise pollution in civilian use, noise reduction of MAV is a goal to achieve. Aeroacoustic research has long been focusing on full-scale rotorcrafts. At MAV scales however, the quantification of the numerous sources of noise is not straightforward, as a consequence of the relatively low Reynolds number that ranges typically from 104 to 105. Reducing the noise generated aerodynamically in this domain then remains an open topic. This two-parts contribution describes a numerical methodology to achieve noise reduction by optimization of MAV rotors. Three different propellers are further analyzed using high-fidelity numerical approaches, including unsteady Reynolds Averaged Navier-Stokes (URANS) simulations and Large Eddy Simulations using a Lattice Boltzmann Method (LES-LBM). That strategy will give insight on the flow features around the propellers yielding solutions to achieve noise reduction. The first part of the contribution focuses on the aerodynamic comparison between the numerical methods and the experimental measurements, in terms of loading distribution along the blade radius and global performances such as thrust and torque. A detailed study has been done also to estimate the typical turbulent scales that is generated by the tip vortex, which impacts the leading edge of the following blade. A direct computation of the far-field noise is also reported for the different blade designs.